A case of completely isolated advanced enteric duplication cyst cancer performed partial pancreatectomy. (2019) - Nakashima, Shinsuke; Yamada, Terumasa; Sato, Go; Sakai, Takaaki; Chinen, Yoshinao; Itakura, Hiroaki; Kato, Ryo; Ueda, Masami; Tsuda, Yujiro; Ohta, Katsuya; Matsuyama, Jin; Ikenaga, Masakazu
Highlights: Duplication cysts commonly have connection to the gastrointestinal tract but the cysts are rarely isolated from gastrointestinal tract. Malignant transformation in isolated duplication cysts is extremely rare. This case of advanced cancer with the isolated intestinal duplication cyst was second reported worldwide. The preoperative diagnosis was suspect of mucinous cystic neoplasm arising from pancreas head and partial pancreatectomy was performed. However, in the pathological findings, this cyst diagnosed advanced enteric duplication cyst cancer and not originated from pancreas. Abstract: Introduction: Enteric duplication cysts are rare and, in addition, isolated enteric duplication cysts are lower morbidity prevalence rate. These cysts lack a connection to the gastrointestinal tract or the adjacent mesenteric vasculature and have only been reported in 10 case reports. In these reports, only two reports were cases with malignant transformation. Our case was a report for the advanced cancer of the isolated enteric duplication cyst. Case presentation: The patient was a 43 year-old woman with slightly abdominal pain and mass formation. The abdominal contrast-enhanced computed tomography showed 130 × 100 × 90 mm huge cystic mass existed in right upper peritoneal cavity. The cystic mass had thickened wall and many enhanced nodules. As these imaging findings suggested a tumor originated from pancreas and the preoperative diagnose was suspect of mucinous cystic neoplasm. In operative findings, the tumor originated from pancreatic head and did not attach to gastrointestinal tract. Final pathology indicated the cyst was an isolated advanced enteric duplication cyst cancer and not originated from pancreas. Conclusion: We experienced an extremely rare case of completely isolated advanced enteric duplication cyst cancer. Unique to this case, the preoperative diagnosis was suspect of mucinous cystic neoplasm arising from pancreas head and partial pancreatectomy was performed. However, in the pathological findings, this cyst diagnosed advanced enteric duplication cyst cancer.